The Effect of Job Fair on Unemployment Reduction Mediated by Job Opportunity - Sudrajad, Eka Yudha; Sawitri, Dyah; Farhan, Djuni (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
Job opportunities and unemployment reduction become priority for human development in Malang City. Therefore, this study will examine the effect of job fair on unemployment reduction moderated by job opportunities. This study purposes are follow: 1) Knowing the effect of job fair on job opportunities in Malang City, 2) Knowing the effect of job fair on unemployment reduction in Malang City, 3) Knowing the effect of job opportunities on unemployment reduction in Malang City, 4) Knowing the effect of job fair on unemployment reduction mediated by job opportunities in Malang City. This is a survey research using explanatory research. This research was conducted in Malang City. This study used samples of 96 respondents. Data was collected using a questionnaire and filled in by respondents. From data obtained, a moderation analysis is done to examine the effect each variable. This research has four findings. First, job fair has positive and significant effect on job opportunities. Second, job fair has positive and significant effect on unemployment reduction. Third, job opportunities have positive and significant effect on unemployment reduction. Job opportunities mediated the effect of job fair on unemployment reduction.